Respuesta :
[tex] \sf{\qquad\qquad\huge\underline{{\sf Answer}}} [/tex]
Let's solve ~
[tex]\qquad \sf \dashrightarrow \:\sf \: \dfrac{d}{dx} (3 {x}^{2} - 9x + 5) {}^{9} [/tex]
we know :
[tex]\qquad \sf \dashrightarrow \:\sf \: \dfrac{d}{dx} ({x}^{n}) = nx {}^{n - 1} [/tex]
So, by using the folowing property with chain rule ~
[tex]\qquad \sf \dashrightarrow \:\mathsf { 9(3x^{2} - 9x + 5)^{8}} \sdot(6x - 9)[/tex]
Answer:
[tex]\dfrac{dy}{dx}=9(6x-9)(3x^2-9x+5)^8[/tex]
Step-by-step explanation:
Given equation:
[tex]y=(3x^2-9x+5)^9[/tex]
To differentiate the given equation, use the chain rule:
Chain Rule
[tex]\textsf{If }\: y=f(u) \:\textsf{ and } \: u=g(x) \textsf{ then}:[/tex]
[tex]\dfrac{dy}{dx}=\dfrac{dy}{du} \times \dfrac{du}{dx}[/tex]
[tex]\textsf{Find } \:\dfrac{dy}{dx}\: \textsf{ if } \:y=(3x^2-9x+5)^9[/tex]
[tex]\textsf{Let }\:y=u^9 \: \textsf{ where }\: u=3x^2-9x+5[/tex]
Differentiate the two parts separately:
[tex]\implies \dfrac{dy}{du}=9u^8 \quad \textsf{and} \quad \dfrac{du}{dx}=6x-9[/tex]
Put everything back into the chain rule formula:
[tex]\begin{aligned}\dfrac{dy}{dx} & =\dfrac{dy}{du} \times \dfrac{du}{dx}\\\\\implies \dfrac{dy}{dx} & = (6x-9) \times 9u^8\\\\& = (6x-9) \times 9(3x^2-9x+5)^8\\\\& = 9(6x-9)(3x^2-9x+5)^8\end{aligned}[/tex]